Within-establishment wage inequality and satisfaction - Ambra Poggi (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
The aim of this paper is to provide fresh empirical evidence on the mechanisms through which wage inequality affects worker satisfaction.Theoretically, the wages of others may affect workers' utility for two main reasons: Workers may derive well-being from their social status (the comparison effect) and/or they may use others' wages to help predict their own future wage (the information effect). The author tests both hypotheses. To do this, she models individual utility from pay as a function of a workers own wage and the earnings of all other workers within the same establishment, and she estimates the model using matched British employeremployee data. The author assumes incomplete information about others' wages. She finds that the comparison effect matters. Interestingly, she also provides some evidence on a positive relation between well-being and inequality. Her results are robust to different specifications and different definitions of the reference group.
Keywords: C25; J28; J31; J33; 330; Satisfaction; comparison income; co-workers; inequality; incomplete information